PENGALAMAN MAHASISWA PPL DALAM PELAKSANAAN PEMBIASAAN POSITIF DI SDN KERTA BARAT - Alyatus; W A Rahmatizzakiyah W A Rahmatizzakiyah; Imam Syafi i M H; Ana Lailak Royyanah; Siti Qamariyah; Lailatul Fitriyah; Wahyu Karyo Utomo (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This study aims to describe the experiences of PPL (Teaching Practicum) students in implementing positive habituation activities at SDN Kerta Barat over a two-month period, from January 7 to March 7, 2026. The study employed a descriptive qualitative approach, with data collected through observation and semi-structured interviews involving PPL students who were directly engaged in the implementation of positive habituation activities at the school. Data were analyzed using the interactive analysis model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing, and the trustworthiness of the data was ensured through technique triangulation. The findings indicate that SDN Kerta Barat consistently and systematically implemented six forms of positive habituation: welcoming students at the school gate, morning exercise, recitation of short Qur’anic chapters or Juz Amma, Friday activities consisting of Dhuha prayer, Yasin recitation, and communal meals, reading literacy activities using storybooks, as well as Friday and Ramadan charity or infaq programs. These six habituation practices were proven to provide comprehensive benefits for students’ character development, encompassing religious, disciplinary, social, emotional, and intellectual aspects. Through direct involvement and assistance in each habituation activity, PPL students gained valuable experiences that strengthened their understanding of character education based on school culture. This experience confirms that students’ character development cannot be achieved solely through classroom instruction, but must be fostered through consistent, holistic habituation practices involving all members of the school community. The results of this study are expected to serve as a reference for other elementary schools in designing and implementing effective and sustainable positive habituation programs.